Revealing relationships between personal resources and coping with organizational change - ŞENVAR, ÖZLEM (My University, 2022)
Organizational change consists of three factors; content, process, and context. Change recipients’ characteristics with these factors provide data for employee reactions and change consequences. This study focuses on employees in terms of their dispositional traits and their coping mechanisms on coping with organizational change (COC). The study aims to examine relationships between personal resources and COC examining traits of self-esteem, optimism, perceived control, general self-efficacy and one situational factor; affective commitment and coping mechanisms. Results reveal that general self-efficacy and perceived control are significant traits on COC. Affective commitment elucidates limited role on COC. Optimism mediates the relationship between affective commitment and COC. Cognitive avoidance, cognitive redefinition and information seeking were observed as coping responses employees adapted in COC. Change agents should consider content, context and process issues in planning or responding change, but also put utmost importance in evaluating employees’ self-efficacy, perceived control potential, information sharing for smooth change period.
Keywords: Coping with organizational change (COC); personal resources; coping responses; affective commitment; self-efficacy; perceived control; optimism